SOLIDARITY ECONOMY IN THE PRISON SYSTEM: REPORT OF AN EXTENSION EXPERIENCE (PRÁXIS EM SAÚDE, 2025)
This abstract aims to present the experience of a university extension project carried out in 2023 at the Assis-SP Penitentiary by students of the Psychology program at UNESP – Faculty of Sciences and Letters (FCLAs), focusing on a critical introduction to the Solidarity Economy with individuals in semi-open prison regimes. Based on the perspective of historical-dialectical materialism, in dialogue with Freirean pedagogy and contributions from the Marxist tradition, the project proposed an approach to the Solidarity Economy not merely as an alternative for income generation, but as a political and educational practice capable of challenging the foundations of capitalist sociality. Thus, the project sought to establish a collective space for listening, training, and political imagination, in which participants were recognized as historical subjects, knowledge producers, and protagonists of social transformation processes.
Keywords: Solidarity Economy; Penitentiary; Popular Education; Psychology